Low complexity detection for SC-FDE massive MIMO systems - Borges, David Oliveira (2016)
Nowadays we continue to observe a big and fast growth of wireless com-munication usage due to the increasing number of access points, and fields of application of this technology. Furthermore, these new usages can require higher speed and better quality of service in order to create market. As example we can have: live 4K video transmission, M2M (Machine to Machine communication), IoT (Internet of Things), Tactile Internet, between many others. As a consequence of all these factors, the spectrum is getting overloaded with communications, increasing the interference and affecting the system's per-formance. Therefore a different path of ideas has been followed and the commu-nication process has been taken to the next level in 5G by the usage of big arrays of antennas and multi-stream communication (MIMO systems) which in a greater scale are called massive MIMO schemes. These systems can be combined with an SC-FDE (Single-Carrier Frequency Domain Equalization) scheme to im-prove the power efficiency due to the low envelope fluctuations. This thesis focused on the equalization in massive MIMO systems, more specifically in the FDE (Frequency Domain Equalization), studying the perfor-mance of different approaches, namely ZF (Zero Forcing), EGD (Equal Gain De-tector), MRD (Maximum Ratio Detector), IB-DFE (Iterative Block Decision Feed-back Equalizer) and a proposed receiver combining MRD (or EGD) and IB-DFE.With this approach we want to minimize the ICI (Inter Carrier Interference) in order to have almost independent data streams and to produce a low complexity code, so that the receiver's performance doesn't affect the total system's perfor-mance, with a final objective of increasing the data throughput in a great scale.